Williams syndrome: reduced orienting to other's eyes in a hypersocial phenotype. - Kleberg, Johan Lundin; Riby, Deborah; Fawcett, Christine; Björlin Avdic, Hanna; Frick, Matilda A.; Brocki, Karin C.; Högström, Jens; Serlachius, Eva; Nordgren, Ann; Willfors, Charlotte (Journal of Autism & Developmental Disorders, 2023)
Williams syndrome (WS) is a rare genetic condition associated with high sociability, intellectual disability, and social cognitive challenges. Attention to others' eyes is crucial for social understanding. Orienting to, and from other's eyes was studied in WS (n = 37, mean age = 23, age range 9–53). The WS group was compared to a typically developing comparison participants (n = 167) in stratified age groups from infancy to adulthood. Typically developing children and adults were quicker and more likely to orient to eyes than the mouth. This bias was absent in WS. The WS group had reduced peak saccadic velocities, indicating hypo-arousal. The current study indicates reduced orienting to others' eyes in WS, which may affect social interaction skills.